Ontario secondary teacher comfort with sexual violence prevention education - Almanssori, Salsabel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This study inquires into teachers’ self-identified comfort in teaching about and preventing sexual violence. A Likert-scale survey was used to collect data from 105 secondary teachers from one public school board in Ontario. Findings suggest that participants tend to be more comfortable with teaching about consent and respectful relationships than gender-based and sexual violence, and more comfortable with intervening in more overt and culturally recognizable sexual violence incidents than those that are subtle. Participants overwhelmingly poorly rated the quality of sexual violence education received both pre-service and in-service. Level of comfort, job insecurity, and level of knowledge were all frequently rated as moderate to extreme barriers to teaching about sexual violence. Implications for sexual violence prevention education are discussed.